Comprehensive Evaluation of IgG, IgM, and Total Antioxidant Capacity in Breast Cancer Patients in Kirkuk: Insights into Immune and Oxidative Stress Markers - Younis, Suzan Aladdin; Saleh, Sayran Sattar (Central Asian Journal of Medical and Natural Science, 2025)
Breast cancer remains the most frequently diagnosed life-threatening malignancy in women and continues to be the leading cause of cancer-related mortality in this population. Globally, it is the second most common cause of cancer-related deaths among women. In Iraq, breast cancer represents the most prevalent form of malignancy among females, accounting for approximately one-third of all documented female cancer cases, according to the most recent data from the Iraqi Cancer Registry ,This study was conducted on a cohort of breast cancer patients and healthy volunteers from Kirkuk Governorate in northern Iraq. A total of 95 participants were enrolled, comprising 50 breast cancer patients and 45 age-matched healthy controls , The primary objective of this study was to assess the circulating levels of Immunoglobulin G (IgG), Immunoglobulin M (IgM), and Total Antioxidant Capacity (TAC) in breast cancer patients and to explore their potential utility as diagnostic or prognostic biomarkers , The findings demonstrated significantly elevated concentrations of IgG and IgM, along with a marked reduction in TAC levels among breast cancer patients when compared to the control group (p < 0.05). These results highlight the critical involvement of immune dysregulation and oxidative stress in the pathophysiology and progression of breast cancer.